Blood cadmium levels and Alzheimer’s disease mortality risk in older US adults - Min, Jin-young; Min, Kyoung-bok (Environmental health, 2016)
Cadmium, a ubiquitous environmental pollutant, exhibits potential neurotoxic risk. Although compelling evidence suggests cadmium accumulation has a role in the formation of amyloid-β plaques and neurofibrillary tangles, which are the hallmarks of Alzheimer's disease (AD) pathogenesis, the supporting evidence in humans is limited and conflicting. In this study, we investigated the association between blood cadmium levels and AD mortality among older adults by analyzing the prospective data from the 1999-2004 Third National Health and Nutrition Examination Survey (NHANES) and the Linked Mortality File. The data were obtained from the 1999-2004 NHANES and the NHANES (1999-2004) Linked Mortality File. A total of 4,064 participants aged ≥60 years old with available blood cadmium data and no other missing information on their questionnaires at baseline were included in this study. AD was denoted as G30 based on the ICD-10 underlying causes of death. Of the 4,064 participants, 51 subjects died as a result of AD. Compared with participants with low blood cadmium levels (≤0.3 μg/L), those with high cadmium levels (>0.6 μg/L) exhibited a 3.83-fold (hazard ratio = 3.83; 95 % CI = 1.39-10.59) increased risk of AD mortality. In the Kaplan-Meier survival curves for cumulative AD mortality, higher levels of blood cadmium showed marginally significant association with increased mortality at baseline and in patients over 60 years of age (p = 0.0684). We observed a significant association between blood cadmium levels and AD mortality among older adults in the US. Our findings suggest that environmental exposure to cadmium may be a risk factor for AD.